Experiences of Pregnant Women Undergoing Prenatal Gentle Yoga at Griya Kamini Gianyar - Dharma, I Dewa Gede Candra; Citrawati, Ni Ketut (Basic and Applied Nursing Research Journal, 2024)
During pregnancy, most women experience psychological and emotional changes, and it is not uncommon for a mother to feel worried about potential problems. Concerns may include the possibility of losing her beauty or the baby being abnormal. Prenatal gentle yoga, a modification of prenatal yoga with a gentle birth approach, is offered at Griya Kamini Gianyar. This practice involves deep yoga therapy to support a healthy and fit pregnancy and labor. This study aimed to understand the experiences of pregnant mothers undergoing Prenatal Gentle Yoga at Griya Kamini Gianyar. The research design used in this study employs a qualitative interpretative method to understand the real experiences of pregnant women undergoing Prenatal Gentle Yoga Therapy at Griya Kamini Gianyar. The research results identified seven major themes: Positive Anticipation, Stress Management, Hope for Socializing, Connecting with Babies, Fitness and Flexibility, Professional Instructor Attitudes, and Managing Pain and Discomfort. The overarching theme identified is Stress Management, indicating that Prenatal Gentle Yoga is practiced by pregnant mothers to manage their emotions and ensure a smooth birth. Overall, yoga can be a valuable tool for pregnant mothers to manage pain and discomfort. With a careful and thoughtful approach, yoga can help pregnant mothers experience a more comfortable pregnancy, both physically and mentally.